2018
DOI: 10.18502/kls.v4i1.1388
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Student Participation in Drug Prevention Programs in Jakarta and Makassar

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Research in Makassar and Jakarta on drug abuse control programs showed low (<20%) participation among adolescent. 7 Another study also showed that less than 25% of adolescents in Makassar utilize reproductive health services. This pattern is due to the limited knowledge of adolescents concerning existing health issues and services.…”
Section: Introductionmentioning
confidence: 99%
“…Research in Makassar and Jakarta on drug abuse control programs showed low (<20%) participation among adolescent. 7 Another study also showed that less than 25% of adolescents in Makassar utilize reproductive health services. This pattern is due to the limited knowledge of adolescents concerning existing health issues and services.…”
Section: Introductionmentioning
confidence: 99%